THE RELATIONSHIP BETWEEN PARENTS' KNOWLEDGE LEVEL AND RATIONALITY OF DRUG USE IN DRUG SELF-MEDICATION MANAGEMENT IN CHILDREN WITH FEVER IN PULOMERAK BANTEN - Lia Nurliana; A. Machron Chairulfakah; Agung Budiyanto (Journal of Industrial Engineering & Management Research, 2023)
Fever in children is a common condition, especially in children under 5 years of age. Parents have an important role in handling children when they have a fever. Different knowledge of mothers will result in different management of fever in children. Self-medication measures for fever in children vary greatly in the community, some are not yet able to do self-medication because there are very high concerns such as fear of seizures and others. There are also those who have been able to do self-medication with physical therapy or drugs (antipyretics), but rationality in using fever medicine for children can be good and it can be bad. Pulomerak sub-district, Banten. Methods: Analytical observational study with a cross-sectional approach. The results of the research number of respondents in this study were 44 mothers with an average age of mothers was 32.68 ± 7.087. Most of the respondents have low education (45.5%). Most of the respondents' occupations were housewives (31.8%) and most of the family income was above the minimum wage. It was found that 52% of the respondents had low knowledge about fever and it was found that 50% of the total respondents had good and bad management of fever. Based on the results of the Chi square test, it was found that the value of p = 0.002 and the prevalence ratio was 7.0 (1.1 to 46.2) so that it can be concluded that there is a significant relationship between the level of knowledge of mothers about fever and the management of fever in children.